Surdez em linhas de fuga: políticas de subjetividades outras na educação inclusiva - Monti, Luísa Leôncio (Universidade Federal de São Carlos, 2023)
The various obstacles imposed on the implementation of the inclusive education have made its effective implementation impossible. As a thesis, I assume that the subjecting violence manifests itself in the inclusive context, through normative logic, activated in the classification and categorization of disabled bodies and their affections. This movement weakens plural forms of life and, therewith, to maintain singularities, some bodies rise up, establishing resistance through lines of flight. In this sense, I aimed to map the practices of (non) violence in inclusive education composed of molar, molecular and lines of flight that act in the production of subjective marks in the deaf ethos. This is a cartographic research, based on a paradigmatic case, carried out in a school unit located in the interior of the state of São Paulo, in the high school stage. In school cartography, I problematized the practices of deaf subjectivation arising from the relations of knowledge and power produced in school discursive practices. I turned to the internal and capillary productions of/in the school, through the eyes of the deaf person, as well as about their insertion in inclusive educational practices. The field research took place on two fronts: observations in the school territory, with entries in a field diary and an interview, as a cartographic procedure. We opted for a cartographic analysis, conceptually based on the philosophies of difference. The theoretical reference came from Michel Foucault, Gilles Deleuze, and Félix Guattari. Were identified, interspersed with the narrative of the life poem, four molar lines (linguistic, physical space, affective and symbolic-religious violence) and four molecular lines (non-violence of the encounter, of being queer, of being umbandista, and other deafness), which guided the discussions. It is believed that the research contributes to recognizing aspects that lead to violence and non-violence in the constitution of subjectivity during the school trajectory of deaf people. In view of the signs found, there is a way of existence, a pragmatic of singularity in the life-poem, and that their voices/experiences in common rooms and the inclusive school stand as local knowledge that resists and announces more ethical practices in favor of differences made along lines of flight.

Los diversos obstáculos impuestos a la realización de una educación inclusiva han imposibilitado su implementación efectiva. Como tesis, asumo que las violencias de sujeción se manifiestan en el contexto inclusivo, por la lógica normativa, activada en la clasificación y categorización de los cuerpos sordos y de sus afectos. Ese movimiento debilita las formas de vida plurales y, con eso, para el mantenimiento de singularidades, algunos cuerpos insurgencia, trazando resistencias por la vía de las líneas de fuga. En ese sentido, objetivé cartografiar las prácticas de (no) violencia en la educación inclusiva compuestas por líneas molares, moleculares y de fuga que actúan en la producción de marcas subjetivas en el ethos sordo. Se trata de una investigación cartográfica, a partir de un caso paradigmático, realizada en una unidad escolar localizada en el interior del estado de São Paulo, en la etapa de la Enseñanza Media. En la cartografía escolar problematicé las prácticas de subjetivación sorda provenientes de las relaciones de saber y poder producidas en prácticas discursivas escolares, y me volví a las producciones internas y capilares de la/en la escuela por la mirada de la persona sorda, así como sobre su inserción en las prácticas educativas inclusivas. La investigación de campo tuvo lugar en dos frentes: observaciones en el territorio escolar, con entradas en un diario de campo y una entrevista, como procedimiento cartográfico. Se optó por un análisis cartográfico con base conceptual en las filosofías de la diferencia. El referencial teórico se dio en Michel Foucault, Gilles Deleuze y Félix Guattari. Fueron identificadas y entremezcladas a la narrativa de la vida-poema, cuatro líneas molares (violencia lingüística, de espacio físico, afectiva y simbólico-religiosa) y cuatro líneas moleculares (no violencia del encuentro, del ser queer, del ser umbandista y sordera otra)que guiaron las discusiones. Se cree que la investigación contribuye para reconocer aspectos que llevan a las violencias y no violencias en la constitución de la subjetividad durante la trayectoria escolar de sordos. Frente a los signos encontrados, se nota un modo de existencia, una pragmática de la singularidad en la vida-poema, y que sus voces/experiencias en salas comunes y en la escuela inclusiva se colocan como saberes locales que resisten y anuncian prácticas más éticas en pro de las diferencias hechas en líneas de fuga.
Deafness in lines of flight, policies of other subjectivities in inclusive education
Sordera en líneas de fuga: políticas de subjetividades otras en la educación inclusiva
Keywords: Educação especial; Surdez; Subjetividade; Violência de sujeição; Linhas de fuga; Special education; Deafness; Subjectivity; Subjecting violence; Lines of flight; Educación especial; Sordera; Subjetividad; Violencia de sujeción; Líneas de fuga; CIENCIAS HUMANAS::EDUCACAO